The impact of a smoke-free psychiatric hospitalization on patient smoking outcomes: a systematic review. (July 2014) - Stockings, Emily A; Bowman, Jenny A; Prochaska, Judith J; Baker, Amanda L; Clancy, Richard; Knight, Jenny; Wye, Paula M; Terry, Margarett; Wiggers, John H
Objective: Smoke-free policies have been introduced in inpatient psychiatric facilities in most developed nations. Such a period of supported abstinence during hospitalization may impact smoking behaviours post discharge, yet little quantitative evidence exists. The aim of this review was to provide the first synthesis of the research evidence examining the impact of a smoke-free psychiatric hospitalization on patients' smoking-related behaviours, motivation, and beliefs. Methods: We conducted a systematic review of electronic databases PubMed, MEDLINE, PsycINFO, and EMBASE from inception to June 2013. Studies were included if they were conducted in an inpatient psychiatric facility with a smoke-free policy and if they examined any change in patients' smoking-related behaviours, motivation, or beliefs either during admission, post discharge, or both. Risk of bias was assessed using the Cochrane Collaboration Risk of Bias Tool. Results: Fourteen studies were included in the review. Of the four studies that assessed change in smoking from admission to post discharge, two indicated a significant decline in cigarette consumption up to 3 months post discharge. Positive changes in motivation to quit and beliefs about quitting ability were identified in two studies. One study reported an increase in the rate of quit attempts and one reported a decline in nicotine dependence levels. Conclusions: A smoke-free psychiatric hospitalization may have a positive impact on patients' smoking-related behaviours, motivation, and beliefs, both during admission and up to 3 months post discharge. Further controlled studies with more rigorous designs are required to confirm this potential.